Neural Correlates of Listening to Varying Synchrony Between Beats in Samba Percussion and Relations to Feeling the Groove - Engel, Annerose; Hoefle, Sebastian; Monteiro, Marina Carneiro; Moll, Jorge; Keller, Peter E. (Frontiers in Neuroscience, 2022)
Listening to samba percussion often elicits feelings of pleasure and the desire to move with the beat – an experience sometimes referred to as “feeling the groove”- as well as social connectedness. Here we investigated the effects of performance timing in a Brazilian samba percussion ensemble on listeners’ experienced pleasantness and the desire to move/dance in a behavioral experiment, as well as on neural processing as assessed via functional magnetic resonance imaging. Participants listened to different excerpts of samba percussion produced by multiple instruments that either were “in sync”, with no additional asynchrony between instrumental parts other than what is usual in naturalistic recordings, or were presented “out of sync” by delaying the snare drums (by 28, 55 or 83 ms). Results of the behavioral experiment showed increasing pleasantness and desire to move/dance with increasing synchrony between instruments. Analysis of hemodynamic responses revealed stronger bilateral brain activity in the supplementary motor area, the left premotor area, and the middle frontal gyrus with increasing synchrony between instruments. Listening to "in sync" percussion thus strengthens audio-motor interactions by recruiting motor-related brain areas involved in rhythm processing and beat perception to a higher degree. Such motor related activity may form the basis for “feeling the groove” and the associated desire to move to music. Furthermore, in an exploratory analysis we found that participants who reported stronger emotional responses to samba percussion in everyday life showed higher activity in the subgenual cingulate cortex, an area involved in prosocial emotions, social group identification and social bonding.